Disciplining Disability under Danish Active Labour Market Policy. (28th March 2012) - Møller, Marie Østergaard; Stone, Deborah
Abstract: This article explores how caseworkers are re‐constructing disability in the Danish welfare system and disciplining themselves and clients according to the active labour policy paradigm. Combining Foucault's ideas about discipline with Maynard‐Moody and Musheno's method of interpreting street‐level bureaucrats' stories (Foucault 1977 ;Maynard‐Moody and Musheno 2003 ), we analyze caseworkers' stories about their clients, fellow caseworkers and themselves to understand how they practice the ideology behind active labour policy. Our analysis usesMøller's (2009 ) interviews with 24 Danish caseworkers who administer social welfare and sick leave benefits based on disability as the primary eligibility criterion. We selected stories told by caseworkers that exemplify archetypes of good and bad citizens, good and bad clients, and good and bad caseworkers. Through interpretative analysis, we elucidate how caseworkers make sense of active labour policy and internalize the pressures of managerial reforms to discipline both citizens and each other.